THE RESEARCH OF VARIATION OF THE PERIOD AND PRECESSION OF THE ROTATION AXIS OF EGS (AJISAI) SATELLITE BY USING PHOTOMETRIC MEASUREMENT - Burlak, N.; Koshkin, N.; Korobeynikova, E.; Melikyants, S.; Shakun, L.; Strakhova, S. (Одеські астрономічні публікації, 2014)
The light curves of EGS Ajisai with temporal resolution of 20 ms referred to the time scale UTC (GPS) with an error of at most 0.1 ms were obtained. The observed flashes are produced when the mirrors which cover the spinning satellite’s surface reflect off the sunlight. In previous paper the analysis of sequence of flashes allowed of reconstructing the arrangement and orientation of the mirrors, i.e. developing an optogeometric model of the satellite (Korobeynikova et al., 2012), and to apply that model along with new photometric observations to determine the satellite’s sidereal rotational period with an accuracy that was previously unachievable. A new technique for determination of the spin-axis orientation during each passage of the satellite over an observation site was developed. The secular slowdown of the satellite’s spin rate (Рsid = 1.4858·EXP(0.000041099·T), where Т is measured in days counted from the date of the satellite launch) and its variations correlating with the average duration of the satellite orbit out of the Earth’s shadow were refined. New parameters of the spin-axis precession were estimated: the period Pprec = 116.44 days, αprec = 18.0h, δprec = 87.66°, the nutation angle θ = 1.78°.